Pendaftaran Tanah Jalan Umum Sebagai Aset Publik di Kota Pariaman - Fara Ditha; Kurnia Warman; Hengki Andora (LPPM Universitas Ekasakti Padang, 2023)
Public road land is a public asset whose control lies with the state. In accordance with Article 9 paragraph (2) of Government Regulation Number 24 of 1997 concerning Land Registration, registration of land whose object is state land is carried out by recording the plot of land in the land register. The State Finance Law and the State Treasury Law provide a different understanding. The central and regional governments are required to certify all land they control without distinguishing between private domains or public domains attached to the objects being registered, so that control over public road land which should belong to the state, changes to the property of a government agency. The research method used is a normative empirical approach which is descriptive qualitative in nature. The results and discussion show that the basis for consideration by the Pariaman City Regional Government for registering public road land is based on Pariaman City Regional Regulation Number 14 of 2017 concerning Management of Regional Property and Pariaman Mayor Regulation Number 58 of 2019 concerning Technical Instructions for Management of Regional Property which was born from a KPK Instruction . Initially, the status of public road land in land administration was state land (TN), but because it was registered in KIB A, the status changed to Hak Pakai (P). The process for registering public road land is the same as registering land for government agencies whose objects are used to carry out the duties of the government agency concerned.